A survey of eating styles in eight countries: Examining restrained, emotional, intuitive eating and their correlates. Issue 1 (8th August 2022) - Markey, Charlotte H.; Strodl, Esben; Aimé, Annie; McCabe, Marita; Rodgers, Rachel; Sicilia, Alvaro; Coco, Gianluca Lo; Dion, Jacinthe; Mellor, David; Pietrabissa, Giada; Gullo, Salvatore; Granero‐Gallegos, Antonio; et al.
Abstract: Introduction: Restrained, emotional and intuitive eating were examined in relation to each other and as correlates of participants' weight status, body image and self‐esteem. In some past research, restrained and emotional eating have been associated with higher weight status and poorer mental health, while intuitive eating is more frequently linked to lower weight status and more positive well‐being. However, these eating styles have rarely been examined together and never in a large cross‐country sample. Method: Six‐thousand two‐hundred and seventy‐two (6272) emerging adults ( M age = 21.54 years, SD = 3.13) completed scales from the Three‐Factor Eating Questionnaire, the Eating Disorders Examination Questionnaire, the Intuitive Eating Scale‐2, the Multidimensional Body Self Relations Questionnaire, the Rosenberg Self‐Esteem Scale, and provided weight and height information that was used to calculate body mass index (BMI). Participants resided in Australia, Belgium, Canada, China, Italy, Japan, Spain and the United States and provided information using an online survey. Results: Path analyses for the entire sample revealed significant pathways between higher intuitive eating and higher body satisfaction and self‐esteem, and lower BMIs among participants. Higher levels of restrained and emotional eating were associated with lower body satisfaction and self‐esteem, and higher BMIs among participants. Minor cross‐country differences were evident in these patterns of relations, but intuitive eating emerged as a consistent predictor across countries. Conclusion: Overall, findings suggest that efforts should be made to increase intuitive eating among emerging adults and to support individual and macrolevel interventions to decrease restrained and emotional eating behaviours.